(untitled) - Sibeko-Matjila, K.P. (Kgomotso Penelope)

Establishment of in vitro persistent infection of the foot-and-mouth disease virus SAT 2 serotype and comparative viral genome analysis during acute and persistent infections (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2024.